Os doze trabalhos de Hércules: a estilização do mito na obra Lobatiana - Oliveira, Diva de (2006)
The aim of this work is a dialogism approach between the basis-text, Héracles de Eurípedes, As metamorfoses de Ovídio and Os Doze de Trabalhos de Hércules by Monteiro Lobato. Firstly, it will be researched how Hercules, the Greek mith was stylised by Monteiro Lobato, throughout the gathering of signs inserted in the dialogical variety text pointing to the likeness and the difference concerning to the basis-texts. It will prosecuted, hence, the meeting between the theory about Mikhail Bakhtin s dialogism and the development about Julia Kristeva s theory related to the Bakhtin s proposals - The intertextuality. It will be still intended to demonstrate how the Taubaté s writer contributed to the formation of the Brazilian childish literature and the improvements idealized by him in several performance fields.